The variable loop 3 in the envelope glycoprotein is critical for the atypical coreceptor usage of an HIV-1 strain. - Yue Xiang; Wei Liu; Yue Chen; Chuntao Zhang; Weiheng Su; Yan Zhang; Jiaxi Sun; Feng Gao; Chunlai Jiang (PLoS ONE, 2014)
The majority of HIV-1 strains enter CD4+ T cells using the CCR5 and/or CXCR4 co-receptor. However, we recently identified a transmitted/founder (T/F) virus (ZP6248) that efficiently used an alternative coreceptor GPR15, rather than commonly used CXCR4 and CCR5, to establish clinical infection. To understand which regions in the env gene were critical for the atypical coreceptor usage, we generated a set of V3 mutants and determined their infectivity in GHOST cells that expressed different coreceptors. When the variable loop 3 (V3) in YU2 was replaced with the ZP6248 V3 (YU2.6248V3), the chimera YU2.6248V3 infected GPR15+ cells but not CCR5+ cells. To determine which amino acids in V3 was responsible for this phenotype change, each of the eight amino acids that differed from the subtype B consensus V3 was substituted with alanine. The G306A and S322A mutations significantly reduced the replication capacity of YU2.6248V3 in GPR15+ cells, while all other alanine substitutions at positions 307, 314, 315, 316, 317 and 318 completely abrogated the infectivity of YU2.6248V3 in GPR15+ cells. The E314A mutation, as the E314G mutation reported before, also rendered the YU2.6248V3 infectious in CCR5+ cells, while none of other alanine mutants could infect CCR5+ cells. These results demonstrated that amino acids in ZP6248 V3 might form a unique conformation that was critical for the interaction with GPR15 while the amino acids at position 314 in the V3 crown of ZP6248 played a key role in interaction with both CCR5 and GPR15. The unique phenotypes of ZP6248 can serve as a model to understand how HIV-1 explores the diverse coreceptor reservoir through novel genetic variants to establish clinical infection.